The effects of erythropoietin on transferrin receptor concentration in rat duodenum tissue - Pittner, Christa (My University, 2008)
Preliminary studies showed factors contained in human milk retain their mitogenic activity following pasteurization. Iron is critical in cell proliferation in early life. Erythropoietin (Epo), a factor found in human milk, stimulates iron utilization, but its role in iron absorption is unclear. We hypothesized that expression of duodenal iron transporter, TfR, would be higher in damfed (DF) or rats with iron deficiency anemia (IDA) fed enteral Epo from postnatal day 4-12, compared to control. Duodenum and liver were stained for iron and duodenal TfR immunohistochemistry was performed. Body or liver iron content was measured. TfR density was higher in IDA, compared to DF (p=0.05). Liver iron content was greater in IDA and IDA+Epo than Dam or Dam+Epo, p<0.0005, but liver Prussian blue staining was lower in IDA and IDA+Epo, compared to Dam or Dam+Epo (p<0.0001). These data support increased TfR density with iron deficiency, but no appreciable effect with Epo.
Effects of iron deficiency and enteral erythropoietin on transferring receptor concentration in newborn rat duodenum
22 p.
Keywords: Biochemistry; Pediatrics